Editorial (Communicate: Journal of Library and Information Science, 2022)
This is Volume 24, Number 2, December, 2022 of Communicate: Journal of Library and Information Science. With the general elections just around the corner, with fake news and non-fake news, the bad and good information, the beautiful and ugly scenarios flying around, I wish to let the general public know that the digital librarian is trained to sift all these and provide you with the AUTHETIC. Therefore, I urge all and Sundry to always have recourse to the library of all types in your community – public, school, Academic, Research and National Libraries. They abound in Nigeria, and are there to serve you.